Preliminary investigations of sustainable magnetic catalyst-based biochar derived spent coffee ground for biodiesel production from waste cooking oil - Silvaraja, Jayaraja; Noor Yahida, Yahya; Muzakkir, Mohammad Zainol; Lee, Yong Siang (Elsevier Ltd., 2025)
Due to the shortage of energy resources and environmental issues, the study presents a sustainable approach for biodiesel production from waste cooking oil (WCO) catalyzed using magnetic catalyst-based biochar derived spent coffee ground (SCG). The added properties of magnetic and basic towards this catalyst was prepared by facile carbonization of one-pot SCG with Fe(III) and potassium hydroxide as activation agent at 700 °C for 2 h The characteristics of the catalyst was analyzed through Fourier transform spectroscopy (FTIR), scanning electron microscope coupled with energy dispersive X-ray (SEM-EDX), x-ray diffraction and Brunauer–Emmett–Teller (BET) surface area analysis. The performance of the catalyst was explored by the parametric effect on biodiesel yield from WCO. The parameters included are methanol to oil molar ratio, dosage of the catalyst and reaction time. The results showed that the catalyst exhibited excellent catalytic activity, with a biodiesel yield of 92.31% under 6:1 methanol to oil molar ratio, 1 wt% of catalyst dosage and 2 h of reaction time and the magnetism observation shows the catalyst own a magnetic property. In addition, the findings suggest that this approach offers a promising contribution for the development of a circular economy in the biofuel industry based on the utilization of waste to wealth.